The divine fury [videorecording (DVD)] - Kim, Joo-Hwan (Director); Kim, Joo-Hwan (Director); Pak, Sŏ-jun, 1988-; Ahn, Sung-Ki; Woo, Do-Hwan (Well Go USA Entertainment, 2019)
Yong-hu, a champion fighter who abandoned his faith after the death of his father, finds himself in the middle of a battle against evil forces when mysterious wounds appear in the palms of his hands.